PENGARUH PENGGUNAAN HANDPHONE TERHADAP POLA TIDUR DAN PERKEMBANGAN EMOSI ANAK KELAS 4 DAN 5 SEKOLAH DASAR NEGERI 1 BENTENGMATI - Nadia Aisya Febriyani; Ali Yusuf; Adira Thifalanajla K; Aira Anastasya; Sekar Dwi Ardianti; Erik Aditia Ismayam A. (JIP: Jurnal Ilmu Pendidikan, 2024)
This study aims to investigate the impact of using mobile phones before bedtime on sleep patterns and emotional development of elementary school children. The research sample consisted of 60 randomly selected children from grades 4 and 5 at Bentengmati 1 Elementary School in Mijen. Data was collected on mobile phone usage before bedtime, sleep patterns, and children's emotional development. The subjects of the study were fourth and fifth-grade students at Bentengmati 1 Elementary School. Data collection techniques included surveys and questionnaires. The primary data for this research was obtained through distributing questionnaires to the fourth and fifth-grade students. The study was conducted online using Google Forms from April 27 to 28, 2024. Data was processed using Microsoft Excel and SPSS Statistics 22. The results showed that students at Bentengmati 1 Elementary School have varying durations of gadget usage. There are 21 students (35%) who have a high duration of gadget use and 10 students (16.7%) with a low duration. The study on the duration of gadget usage among fourth and fifth-grade students at Bentengmati 1 Elementary School revealed that these children find gadgets very important and have difficulty controlling their use. This condition is common among children transitioning from childhood to adolescence, who still require parental supervision. The data also revealed that more than half of the students experience poor sleep quality, with 21 students (35%) affected. Additionally, 68 out of 81 respondents (84%) reported poor sleep quality, while only 13 students (16%) had good sleep quality.